Student Centered Learning in English Study - Winarsih Winarsih; Yatno Yatno (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
A highlight of the Indonesian National Curriculum 2014 is the proposed shift in emphasis in teaching methods to a Student Centered Learning SCL of communicative approach. It has major pedagogical benefits, which are particularly relevant to language learning. This is to identify and to know how the responsibility of SCL puts on learners, for their own learning by using variety of English language actively as medium of instruction during class. It involves students in more decision-making processes, and learn English by doing rather than just by listening and performing meaningless tasks which are often not in context, and therefore unreal to them. They are 90% doing participating and the real thing while students practicing English for real-world skills. Learning becomes more active and memorable: because it is personalized, relevant to the students own lives and experiences, it brings English use alive, and makes it relevant to the real world. The more actively involved students are in their own learning, the more they are likely to remember what they learn. By using communicative activity, English again becomes more real and part of the students lives.